Analisis Kerusakan Track Adjuster Pada Excavator Kelas 20 Ton - Anwari, Muhammad; Nugroho, Danuarta Adi; Rosyid, Fakih Aulia; Bagaskara, Pagi Singgamata; Wibowo, Tegar Taufik; Pratama, Bagus Ardyansyah Ilham; Krisnaputra, Radhian; Aisyah, Nyayu (Jurnal Teknologi dan Rekayasa Alat Berat, 2025)
The track adjuster is an important component on the excavator wheel that serves to adjust the tension of the track chain and reduce drag on the front of the excavator unit. When the excavator wheels are active (loading or digging), the track adjuster becomes the main support, especially when moving. The undercarriage of the excavator has to deal with road or soil structure resistance as it is in direct contact with the surface. A wear and tear analysis of the track adjuster shaft on industry Y's excavator X revealed several problems: broken spring, track piston with scratches, leaking seal and rusted rod. Corrective measures involved replacing the damaged components with new ones. In addition, routine maintenance includes cleaning the unit to facilitate checking the undercarriage, especially the track adjuster. With proper maintenance, the life of these components can be extended and excavator performance optimized.